Geological Modelling of Sandstones Formations and Petrophysical Characterization of Hydrocarbon Reservoirs in the Termit Basin, Eastern Niger: Case of the Goumeri Prospect - Laouali Ibrahim Sarki; Bohari Abdou Dodo; Vitaline Vanessa Morabo Okoletiomou; Moussa Harouna (European Scientific Journal, ESJ, 2022)
The general objective of this study, which focuses on the geological modelling of sandstone formations and petrophysical characterization of hydrocarbon reservoirs in the Termit basin, is to build a geological model to visualize the geometry of reservoir formations. Its specific objectives are: (1) determine the extension of promising reservoir formations, (2) establish models of petrophysical parameters (porosity, permeability and saturation). The methodology implemented is based on the integration of lithological data and petrographic parameters from the logs into the Petrel software.  The interpretation of the results obtained on geological modelling shows; geometry and extension of reservoir formations in the form of sand lenses of varying thickness from one prospect to another.  Petrophysical parameter models including porosity and permeability models have made it possible to understand the vertical distribution of the different reservoir units.